2017
DOI: 10.12968/bjon.2017.26.14.813
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of interprofessional education 10 years on

Abstract: Inter Professional Education (IPE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 27 publications
(29 reference statements)
0
24
0
18
Order By: Relevance
“…A systematic review conducted by Reeves et al () attempted to investigate the effectiveness of IPE interventions in practicing healthcare professionals and found that while some studies did report positive outcomes, the heterogeneity in the type of IPE interventions makes it impossible to draw generalizable inference for the effectiveness of IPE. In accordance, Illingworth and Chelvanayagam's () review article also found that there is little conclusive evidence to show the benefits of IPE, specifically relating to health outcome and more research was needed to show that patients and health care providers benefit from IPE. Thus, future research should focus on the effectiveness of IPE in the clinical environment and practicing healthcare professionals and whether there is any impact on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review conducted by Reeves et al () attempted to investigate the effectiveness of IPE interventions in practicing healthcare professionals and found that while some studies did report positive outcomes, the heterogeneity in the type of IPE interventions makes it impossible to draw generalizable inference for the effectiveness of IPE. In accordance, Illingworth and Chelvanayagam's () review article also found that there is little conclusive evidence to show the benefits of IPE, specifically relating to health outcome and more research was needed to show that patients and health care providers benefit from IPE. Thus, future research should focus on the effectiveness of IPE in the clinical environment and practicing healthcare professionals and whether there is any impact on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Training for healthcare professionals has traditionally been delivered in profession‐specific silos with restricted opportunities for students to learn about and interact with other healthcare professionals. This separation persists even though the course material is often essentially the same and the students will work with other professionals when they enter a clinical setting (Gilligan et al, ; Illingworth and Chelvanayagam, ). This lack of interprofessional education (IPE) may result in patients “falling through the cracks” because of the lack of collaboration and poor communication between healthcare professionals (Olson and Bialocerkowski, ).…”
Section: Introductionmentioning
confidence: 99%
“…Benzer bir yaklaşım ile Barker, Bosco ve Oandasan 32 , MAE alanında çalışanların öncelikle dil, fikir, prensip ve zaman birliği sağlamak için çalışmaları gerektiğine dikkat çekmişlerdir. MAE yaklaşık 20 yıldır gündemde olmasına rağmen günümüzde hala mesleklerarası kavramı multiprofesyonel gibi benzer kavramlar ile karıştırılmaktadır 5 ayarlamak en önemli sorunlardan biridir 10,22,31,32 . MAE programlarının öğrencilerin deneyim, hazırbulunuşluk, mesleki bilgi, beceri ve tutum düzeylerinin birbirine yakın olduğu bir dönemde hayata geçirilmesi de zaman sorunu içerisinde ele alınabilmektedir 11 .…”
Section: Discussionunclassified
“…MAE'in; öğrencilerin, işbirliği ve ekip çalışması becerilerini geliştirme [15][16][17] ; sağlık profesyonellerinin, meslekler arasındaki bariyerlerinin kırılmasına yardımcı olma 18 ve iş doyumunu arttırma 19 , hasta ve sağlık sistemi açısından; bakımının kalitesini ve güvenliğine ilişkin çıktıları iyileştirme 16 , hasta memnuniyetini arttırma 13 , hata oranlarını azaltma 20,21 gibi pek çok yararı bulunmaktadır. Dünya Sağlık Örgütü (DSÖ), 2010 yılında yayınladığı Mesleklerarası Eğitim ve İşbirlikli Uygulamalar İçin Eylem Planı'nda etkili MAE uygulamalarının etkili işbirliğini mümkün kıldığına dair yeterince kanıt bulunduğunu bildirmiştir 10 . MAE'in sağlıklı/hasta birey, sağlık çalışanları, öğrenci ve sağlık sistemi üzerine olan olumlu etkilerine rağmen eğitim kurumları, MAE programlarının hayata geçirilmesi sürecinde pek çok sorun ile karşılaşmaktadır 4,9,22 .…”
Section: Introductionunclassified
“…While a long-term higher educational goal is the inclusion of interprofessional educational opportunities as part of any degree program, this takes cooperation, coordination, and time, and few successes are demonstrated in universities around the world (Chen, Delnat, & Gardner, 2015). Therefore, extracurricular inter-professional educational opportunities remain critically recommended to more effectively advance the skills and knowledge of pre-service/undergraduate students (Illingworth, & Chelvanayagam, 2017). The purpose of this article is to describe an extracurricular case competition model, whereby students engage in experiential learning outside of the traditional classroom model, and have the opportunity to challenge themselves competitively in multidisciplinary groups guided by faculty and inspired by professionals in their respective fields.…”
mentioning
confidence: 99%